Influence of Effective Parameters on Product Gas Ratios in Sorption Enhanced Gasification. (2016) - Ammar, Muhammad; Mutalib, M. I. Abdul; Yusup, Suzana; Inayat, Abrar; Shahbaz, Muhammad; Ali, Basit
Abstract: Biomass steam gasification for the production of syngas is a promising alternative for producing clean energy to substitute fossil fuels and reduce the carbon footprints. Even though the gasification process is not a new technology, there have been limited studies on the process simulation to analyze the gasification behavior. In this research work a mathematical approach was implemented in order to evaluate the effective parameters for steam gasification of palm waste.The final product gas composition was selected as the benchmark to assess the effect of process parameters on gasification behavior. The validated of developed mathematical model was done using the experimental data for steam gasification of biomass along with the experimental data for sorption enhanced steam gasification of biomass.